2020
DOI: 10.1016/j.cognition.2020.104349
|View full text |Cite
|
Sign up to set email alerts
|

Shared contributions of the head and torso to spatial reference frames across spatial judgments

Abstract: Egocentric frames of reference take the body as the point of origin of a spatial coordinate system. Bodies, however, are not points, but extended objects, with distinct parts that can move independently of one another. We recently developed a novel paradigm to probe the use of different body parts in simple spatial judgments, what we called the misalignment paradigm . In this study, we applied the misalignment paradigm in a perspective-taking task to investigate whether the weightings gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…Stimuli for the Misalignment Paradigm were similar to our previous studies (Alsmith et al 2017;Longo et al 2020) and are shown in Fig. 1A.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Stimuli for the Misalignment Paradigm were similar to our previous studies (Alsmith et al 2017;Longo et al 2020) and are shown in Fig. 1A.…”
Section: Methodsmentioning
confidence: 94%
“…The analysis was similar to that used in our previous study (Alsmith et al 2017;Longo et al 2020). Best-fitting cumulative Gaussian functions were fit using maximum-likelihood estimation for each participant in each condition using the Palamedes toolbox for MATLAB (Mathworks, Natick, MA, Prins and Kingdom (2009), available online at: http:// www.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations